The Effect of Benefits, Job Rotation and Job Promotion on Employee Performance of PT X Cilegon City - Salsa, Syahla Rania; Dewi, Santi Riana (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study's objectives are to determine whether benefits, job rotation, and job promotion affect employee performance at PT X Kota Cilegon. Quantitative research methodologies were used to conduct this study. The population of the study was all employees at PT X Kota Cilegon totaling 403 employees. The probability sampling method using the Slovin formula with a 10% margin error at PT X Kota Cilegon totaling 80 respondents. A Google Forms-distributed questionnaire was used to gather data. The SPSS version 27 software was utilized as the data analysis tool in this study. This study used an instrument test to see the validity and reliability test values, and used a classical assumption test to see the normality test whether the data was normally distributed, as well as a t-hypothesis test (partial) to test the influence between variables and the f test (simultaneous) to test the influence together. The results of this study show that (1) Benefits have a positive and notable effect on employee performance, (2) Job Rotation has a positive and notable effect on employee performance, (3) Job Promotion has a positive and notable effect on employee performance.